Supporting Supply Chain Planning with APS Class Systems: A Case Study of SAP IBP - Advantages and Challenges - Michał JAKUBIAK (Communications of International Proceedings, 2024)
Alongside Enterprise Resource Planning (ERP) systems, which primarily support individual business management, an increasing number of companies are investing in Advanced Planning Systems (APS) to bolster planning processes across the supply chain. In this paper, the author presents a different approach to planning processes in the supply chain that can be observed in the literature. The role of APS class systems in supply chain management is also described, and in particular the benefits resulting from the implementation of the SAP IBP system. Using a survey and in-depth interviews, the author tries to identify the main problems and challenges faced by companies implementing APS systems and consulting companies implementing these systems. Based on the respondents' experience (approximately 71% of respondents have been working with APS systems for more than 10 years), the author selected the main challenges that should be addressed during the implementation of the SAP IBP system and those that determine its correct operation. The author explores a subject that is seldom addressed in the existing literature, as it lies at the intersection of supply chain management, planning and IT systems.
Keywords: APS Systems; SAP IBP; Supply Chain; Planning